2016
DOI: 10.1002/pssa.201532923
|View full text |Cite
|
Sign up to set email alerts
|

Role of a‐Si:H in lateral growth of crystalline silicon nanowires using Pb and In catalysts

Abstract: Growth of crystalline silicon nanowires at low temperatures by chemical vapour deposition is an important technological challenge for electronic and sensor nanodevices. Here we present a comparative study of crystalline silicon nanowire growth by plasma‐enhanced chemical vapour deposition (PECVD) using lead and indium. We compare two different growth methods that produce either in‐plane or out‐of‐plane crystalline Si nanowires (SiNWs) at temperatures below 400 °C depending on the growth conditions and the cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The experimental observations of metal-catalyzed SiNWs under plasma in this and previous studies [1,10,16,20,21] have shown that the nanowire growth is a highly complex process where many competing mechanisms play a role and are mutually interlinked. The growth of SiNWs in PECVD is governed by both catalytic and non-catalytic processes.…”
Section: Growth Mechanism Of Metal-catalyzed Nanowires Under the Plasmamentioning
confidence: 52%
See 4 more Smart Citations
“…The experimental observations of metal-catalyzed SiNWs under plasma in this and previous studies [1,10,16,20,21] have shown that the nanowire growth is a highly complex process where many competing mechanisms play a role and are mutually interlinked. The growth of SiNWs in PECVD is governed by both catalytic and non-catalytic processes.…”
Section: Growth Mechanism Of Metal-catalyzed Nanowires Under the Plasmamentioning
confidence: 52%
“…As can be seen, the number of catalytically active nanoparticles is very low compared to the total number of the deposited Sn nanoparticles, typically around 3%. Even lower nucleation density of SiNWs in PECVD has been found for other catalytic metals, such as Au, In, Pb and Ga [16,17].…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations